How do methods of non-fatal self-harm relate to eventual suicide? - Bergen, H; Hawton, K; Waters, K; Ness, J; Cooper, J; Steeg, S; Kapur, N (2012)
Background: Methods used at an index episode of non-fatal self-harm may predict risk of future suicide. Little is known of suicide risk associated with most recent non-fatal method, and whether or not change in method is important. Methods: A prospective cohort of 30,202 patients from the Multicentre Study of Self-harm in England presenting to six hospitals with self-harm, 2000-2007, was followed up to 2010 using national death registers. Risks of suicide (by self-poisoning, self-injury, and all methods) associated with recent method(s) of non-fatal self-harm were estimated using Cox models. Results: Suicide occurred in 378 individuals. Cutting, hanging/asphyxiation, CO/other gas, traffic-related and other self-injury at the last episode of self-harm were associated with 1.8 to 5-fold increased risks (vs. self-poisoning) of subsequent suicide, particularly suicide involving self-injury. All methods of self-harm had similar risks of suicide by self-poisoning. One-third who died by suicide used the same method for their last self-harm and for suicide, including 41% who self-poisoned. No specific sequences of self-poisoning, cutting or other self-injury in the last two non-fatal episodes were associated with suicide in individuals with repeated self-harm. Limitations: Data were for hospital presentations only, and lacked a suicide intent measure. Conclusions: Method of self-harm may aid identification of individuals at high risk of suicide. Individuals using more dangerous methods (e.g. hanging, CO/other gas) should receive intensive follow-up. Method changes in repeated self-harm were not associated with suicide. Our findings reinforce national guidance that all patients presenting with self-harm, regardless of method, should receive a psychosocial assessment. © 2011 Elsevier B.V. All rights reserved.